Resistance and the city challenging urban space - Ehland, Christoph 1971-; Fischer, Pascal (Spatial practices, 2018)
Intro -- Resistance and the City: Challenging Urban Space -- Copyright -- Contents -- Acknowledgements -- General Introduction -- Introduction: Challenging Urban Space -- Part 1 Contested Civic Spaces in the Seventeenth and Eighteenth Centuries -- 1 Civic Subversion in London's Public Rituals in the Seventeenth Century -- 2 The Earl of Rochester: Sexual Politics, Riots and the Chaos of the Carnivalesque -- 3 Rus in Urbe: Parks in Eighteenth-Century Cities -- 4 The Slippery Slope to the Gallows: Crime and Punishment in Early Eighteenth-Century London -- Part 2 Urban Rioting in the Eighteenth and Nineteenth Centuries -- 5 Giving Meaning to Anarchy: Contemporary Interpretations of Rioting in 18th-Century Britain -- 6 Blending Spaces: The Gordon Riots in Literature -- 7 The "Capital of Discontent"? Urban Resistance in Manchester -- Part 3 Reimagining Urban Space -- 8 Creating Situationist Ambiences: Peter Ackroyd's London: The Biography -- 9 Reshaping the City: The Eruv as Stealth Architecture -- 10 Challenging Urban Realities in Recent London Writing: Iain Sinclair's Ghost Milk and John Lanchester's Capital -- Part 4 Creative Transformations of the City -- 11 Critical Urban Studies and/in "Right to the City" Movements: The Politics of Form in Activist Cultural Production -- 12 Street Art as Reclaiming the Streets -- 13 Graffiti as a Place of Resistance in British Poetry -- 14 The Berlin Wall as Mobile Ruin -- Index.